The reliability of retinal nerve fiber layer analysis to differentiate between papilledema and pseudopapilledema: A systematic review - Lourisa Ruth Eldinia; Rona Ali Badjrai; Lazuardiah Anandi; Fierda Ovita Azhari; Erika Anggraini; Brigitta Marcia; Syntia Nusanti (Indian Journal of Ophthalmology)
Differentiating between papilledema and pseudopapilledema can be challenging in certain cases. Relying solely on subjective clinical examination may lead to confusion, and objective diagnostic confirmation methods may pose challenges such as cost, operator dependency, invasiveness or limited availability. This study seeks to assess whether retinal nerve fiber layer (RNFL) analysis can serve as a reliable measurement for establishing the diagnosis. A thorough literature search was conducted on PubMed, ProQuest, Google Scholar and Cochrane from 2012 to 2023, with the last search conducted on March 26, 2023. Non-English studies, review articles, case studies and editorial letters were excluded. The inclusion criteria comprised studies with available full text containing both papilledema and pseudopapilledema groups, with outcomes on sensitivity, specificity and/or area under the curve (AUC). This study adhered to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guideline. A total of 510 participants were included from seven different studies, all encompassing groups of papilledema and pseudopapilledema with or without optic disc drusen (ODD). The studies demonstrated the favorable accuracy of RNFL in differentiating papilledema from pseudopapilledema, with AUC values ranging from 0.78 to 0.91. However, specificity and sensitivity varied between 65%–100% and 33%–91%, respectively. Lower accuracy was observed when pseudopapilledema included only patients with ODD or when papilledema was limited to mild cases. In conclusion, RNFL proves to be a reliable measurement for differentiating papilledema from pseudopapilledema.